2016
DOI: 10.3390/ijms17122146
|View full text |Cite
|
Sign up to set email alerts
|

Insights on Molecular Mechanisms of Chondrocytes Death in Osteoarthritis

Abstract: Osteoarthritis (OA) is a joint pathology characterized by progressive cartilage degradation. Medical care is mainly based on alleviating pain symptoms. Compelling studies report the presence of empty lacunae and hypocellularity in cartilage with aging and OA progression, suggesting that chondrocyte cell death occurs and participates to OA development. However, the relative contribution of apoptosis per se in OA pathogenesis appears complex to evaluate. Indeed, depending on technical approaches, OA stages, cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
220
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(239 citation statements)
references
References 270 publications
10
220
2
1
Order By: Relevance
“…Although the role of the inflammatory process in the development and evolution of OA was initially underestimated, we now understand the importance of the inflammation in OA pathogenesis. Nitric oxide and ROS have been shown to modify the effects of TGF-B and expression of NF-κB-dependent genes [21]. The alteration in the expression and functioning of TGF-B is related to the development of OA [22].…”
Section: Inflammation As Part Of the Pathophysiological Processmentioning
confidence: 99%
“…Although the role of the inflammatory process in the development and evolution of OA was initially underestimated, we now understand the importance of the inflammation in OA pathogenesis. Nitric oxide and ROS have been shown to modify the effects of TGF-B and expression of NF-κB-dependent genes [21]. The alteration in the expression and functioning of TGF-B is related to the development of OA [22].…”
Section: Inflammation As Part Of the Pathophysiological Processmentioning
confidence: 99%
“…Interleukin (IL)-1β, a major pro-inflammatory cytokine produced by chondrocytes and synovial cells, contributes to increased chondrocyte apoptosis [1,2,3], along with the synthesis of other inflammatory mediators, including matrix metalloproteinase (MMP), cyclooxygenase-2 (COX-2) and prostaglandin E2 (PGE 2 ). These inflammatory mediators ultimately inhibit type II collagen and aggrecan synthesis, increase extracellular matrix (ECM) degradation, and cause articular cartilage damage [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An imbalance between anabolism and catabolism of extracellular matrix (ECM) components is the central feature in cartilage destruction. 1) The massive loss of ECM results from cleavage of type II collagen and aggrecan, a predominant proteoglycan, and the consequent release of GAG which is covalently linked to core proteins to form proteoglycans. 28) MMPs, a family of proteolytic enzymes, play pivotal role in the degradation of ECM and mediate cartilage destruction and joint erosion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that cartilage destruction in OA results from inflammation-induced matrix metalloproteinase (MMP) activation. 1) Furthermore, compelling studies reported that chondrocyte cell death such as apoptosis and necrosis participates in OA development, which appears to be complex. 2) Despite extensive studies on cartilage loss and degradation in OA, the exact pathologic mechanisms are not fully understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation